Since variable is raised to a variable power in this function, the common rules of differentiation do not work. First, you need to apply the natural logarithm both sides, such that:

`ln y = ln(x^x)`

Using properties of logarithm, yields:

`ln y = x*ln x`

Differentiating both sides, yields:

`(1/y)*y' = x'*ln x + x*(ln x)'`

`(1/y)*y' = ln x + x*(1/x)`

Reducing like terms, yields:

`(1/y)*y' = ln x + 1`

`y' = y*( ln x + 1)`

Replacing `x^x` for y, yields:

`y' =(x^x)*( ln x + 1)`

Hence, evaluating the derivative of the function, using logarithmic differentiation, yields `y' =(x^x)*( ln x + 1).`

## We’ll help your grades soar

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now